Effects of saffron supplementation on glycemia and inflammation in patients with type 2 diabetes mellitus: A randomized double-blind, placebo-controlled clinical trial study. Issue 4 (July 2020) - Mobasseri, Majid; Ostadrahimi, Alireza; Tajaddini, Aynaz; Asghari, Samira; Barati, Meisam; Akbarzadeh, Moloud; Nikpayam, Omid; Houshyar, Jalil; Roshanravan, Neda; Alamdari, Naimeh Mesri
Abstract: Background: New evidence indicates that overproduction of pro-inflammatory cytokines is responsible for the development of diabetes difficulties. Some herbals such as saffron, may control inflammation and improve the hyperglycemic states in diabetic patients. Therefore, this investigation aimed to assess the effects of saffron supplementation on fasting glucose and inflammatory markers levels in patients with type2 diabetes mellitus (T2DM). Methods: In this randomized double-blind, placebo-controlled clinical trial, 60 T2DM patients were randomly assigned into two groups as saffron and placebo (n = 30) receiving 100 mg/day saffron powder or starch capsules (1 capsule) for a duration of 8 weeks. Fasting blood sample was collected at baseline and at the end of the intervention. Fasting blood glucose (FBG) was immediately analyzed by the auto-analyzer. The serum level of Interleukin −6 (IL-6), Tumor necrosis factor-alpha (TNF-α), and Interleukin-10 (IL-10) were measured using ELISA assay by laboratory kits. Also, Real-time quantitative reverse transcription (RT-PCR) assay measured the expression level of TNF-α, IL-6, and IL-10 at the mRNA level. Results: Saffron supplementation significantly decreased the FBG levels within 8 weeks compared to placebo (130.93 ± 21.21 vs 135.13 ± 23.03 mg/dl, P = 0.012). Moreover, the serum level of TNF-α notably reduced in the saffron group compared to the placebo group (114.40 ± 24.28 vs 140.90 ± 25.49 pg/ml, P < 0.001). Also, saffron supplementation significantly down-regulated the expressions of TNF-α (P = 0.035) and IL-6 mRNA levels (P = 0.014). Conclusion: In our study, it was indicated that saffron modulates glucose levels as well as inflammation status in T2DM patients through decreasing the expressions levels of some inflammatory mediators. Also, further investigations are necessary to confirm the positive effects of saffron as a complementary therapy for T2DM patients. Highlights: In this study, saffron powder supplementation decreased blood glucose levels in patients with type 2 diabetes mellitus. Saffron intake significantly decreased inflammation especially IL-6 and TNF-a levels. Saffron as a food ingredient may promote several beneficial physiological effects in diabetic patients.